2014
DOI: 10.1007/s12034-014-0109-z
|View full text |Cite
|
Sign up to set email alerts
|

Electrical impedance spectroscopy measurements to estimate the uniaxial compressive strength of a fault breccia

Abstract: Fault breccias are usually not suitable for preparing smooth specimens or else the preparation of such specimens is tedious, time consuming and expensive. To develop a predictive model for the uniaxial compressive strength (UCS) of a fault breccia from electrical resistivity values obtained from the electrical impedance spectroscopy measurements, twenty-four samples of a fault breccia were tested in the laboratory. The UCS values were correlated with corresponding resistivity values and a strong correlation be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…As shown in Figure 6 a, The EIS can be visualized by displaying the modulus and phase angle of the impedance as a Nyquist plot on the complex plane [ 22 ]. In the Nyquist diagram, frequency increases from right to left and the EIS is composed of arcs, corresponding to high-frequency impedance, and straight lines, corresponding to low-frequency impedance.…”
Section: Methodsmentioning
confidence: 99%
“…As shown in Figure 6 a, The EIS can be visualized by displaying the modulus and phase angle of the impedance as a Nyquist plot on the complex plane [ 22 ]. In the Nyquist diagram, frequency increases from right to left and the EIS is composed of arcs, corresponding to high-frequency impedance, and straight lines, corresponding to low-frequency impedance.…”
Section: Methodsmentioning
confidence: 99%
“…Afterwards, they used a cerchar abrasivity index for assessing the triaxial strength of Misis fault bimrock. 22 Slatalla and Kahraman 23 analyzed the acoustic emission responses of a fault bimrock, and revealed the influence of block content on the fracture signatures. Kato and Hirono 24 revealed the correlation between the mesoscopic structure and frictional strength of two kinds of fault gouge and a fault breccia, they found that the frictional strength of breccia is larger than the gouge.…”
Section: Introductionmentioning
confidence: 99%
“…Limited studies have been performed on fault breccia (a strong weld bimrock) under static uniaxial compression to obtain its compressive strength. 21,22 However, the weathering actions in the open-pit slope or underground mine results in the further fragmentation of fault bimrock, and fault rock is typically unweld or weak weld bimrocks that are composed of rock blocks and soil particles. Therefore, investigation on the mechanical response of fault rocks considering its mesoscopic structure is needed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations